Trans-perovskite solar cell and preparation method thereof
By modifying and modifying the surface of the hole transport layer and introducing a hafnium oxide passivation layer between it and the perovskite absorbing layer, the problem of high interface defect density of NiOx-based perovskite solar cells is solved, and the photoelectric conversion efficiency and stability of the device is significantly improved, providing technical support for industrialization.
Patent Information
- Application Number
- CN202411995775.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
The high defect density at the interface of NiOx-based perovskite solar cells leads to interface recombination and degradation of perovskite absorbing layers, limiting the performance and stability of the device.
The surface of the hole transport layer is modified and modified by an oxidant, and hafnium oxide is introduced as a passivation layer between the hole transport layer/perovskite absorption layer to reduce the interfacial chemical reaction and degradation and reduce the defect density.
The photoelectric conversion efficiency, light stability and high humidity and high thermal stability of perovskite solar cells have been improved, paving the way for the industrialization of perovskite solar cells.
Smart Images

Figure CN119836106A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of microbial preparations, and specifically relates to an inverted perovskite solar cell and a preparation method thereof. Background Art
[0002] Organic-inorganic halide perovskite semiconductor materials have the advantages of high absorption coefficient, large carrier mobility, adjustable band gap and bipolar carrier transport, as well as relatively low defect density and excellent defect tolerance. The above characteristics make them have great potential in the photovoltaic field. At present, the highest photoelectric conversion efficiency of single-junction perovskite solar cells has reached 26.2%, which is close to the highest efficiency of crystalline silicon solar cells and has the advantages of theoretical low cost and easy preparation. It is one of the most active research directions in the current materials and energy fields. However, as a competitor to traditional commercial solar photovoltaic products, perovskite solar cells must also be comparable in stability. The long-term stability of perovskite solar cells remains the most important challenge facing the commercialization of emerging photovoltaics.
[0003] Inverse perovskite solar cells have attracted much attention due to their low energy consumption, simple structure, low temperature and high cost performance. The performance of the device depends largely on the hole transport layer (HTL) of the inverse perovskite solar cell. The bottom contact not only plays the role of an electron barrier, but also serves as a substrate for growing perovskite. Common materials for the hole transport layer include organic hole materials such as PEDOT:PSS or PTAA, which have a wide band gap (3.6-4.0eV) and can provide high optical performance transparency and energy level alignment. Compared with organic hole transport layer materials, nickel oxide (NiO x ) materials show the advantages of convenient large-area manufacturing, thermal stability, chemical stability, and low cost. However, high-valent nickel and active hydroxyl (-OH) can decompose perovskite, and Ni 3+ It is beneficial to the performance of semiconductor holes, but it will cause iodide oxidation at high temperature, NiO x The surface hydroxyl groups cause the deprotonation of the perovskite cations, resulting in NiO x / perovskite interface. In addition, NiO x There are also disadvantages such as low conductivity, hydrophobicity and mismatch with the energy level of the perovskite absorption layer. To this end, various surface modification techniques have been proposed to passivate NiO x / perovskite interface. For example, UV-ozone and oxygen plasma treatments can increase the x The wettability of the surface promotes the formation of a stable surface state, ultimately improving the NiO x In addition, organic molecules and alkali salts are common surface passivators that can improve the alignment of energy levels. However, the above methods are expensive and difficult to apply to large-area modules.
[0004] In summary, NiO x The main disadvantage of NiO-based PSCs is x The high defects at the NiO / perovskite interface lead to interfacial recombination and degradation of the perovskite absorber layer, thus limiting the x Performance and stability of PSCs.
[0005] Therefore, how to reduce NiO x It is a technical problem to be solved urgently to improve the defect density and non-radiative recombination at the / perovskite interface, enhance the carrier transport performance, and inhibit the degradation of the perovskite absorption layer, thereby improving the conversion efficiency and stability of the device. Summary of the invention
[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide an inverted perovskite solar cell and a preparation method thereof. On the one hand, the present invention uses an oxidant to modify the surface of the hole transport layer, which greatly improves the conductivity and hole transport capacity of the hole transport layer. On the other hand, hafnium oxide is introduced between the hole transport layer / perovskite absorption layer to passivate the interface. Since hafnium oxide has poor reactivity and carries a negative fixed charge, the chemical reaction between the modified hole transport layer and the perovskite absorption layer can be greatly reduced, inhibiting its degradation of the perovskite absorption layer, and effectively changing the concentration distribution of carriers near the heterojunction, thereby reducing the defect density at the interface, reducing interface recombination and photovoltage loss; and the passivation treatment of the passivation layer is conducive to the growth of perovskite and the uniform deposition of a large area of perovskite absorption layer. Therefore, the above-mentioned improvement strategy effectively improves the photoelectric conversion efficiency, light stability and high humidity and high heat stability of perovskite solar cells, paving the way for the industrialization of perovskite solar cells.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides an inverted perovskite solar cell, comprising a conductive substrate, a hole transport layer, a passivation layer, a perovskite absorption layer, an electron transport layer and an electrode which are stacked.
[0009] Wherein, the surface of the hole transport layer on one side close to the passivation layer is modified by an oxidant, and the material of the passivation layer is hafnium oxide.
[0010] On the one hand, the present invention uses an oxidant to modify the surface of the hole transport layer, greatly improving the conductivity and hole transport capacity of the hole transport layer. On the other hand, hafnium oxide is introduced between the hole transport layer / perovskite absorption layer to passivate the interface. Since hafnium oxide has poor reactivity and carries a negative fixed charge, the chemical reaction between the modified hole transport layer and the perovskite absorption layer can be greatly reduced, inhibiting its degradation of the perovskite absorption layer, and effectively changing the concentration distribution of carriers near the heterojunction, thereby reducing the defect density at the interface, reducing interface recombination and photovoltage loss; and the passivation treatment of the passivation layer is conducive to the growth of perovskite and the uniform deposition of a large area perovskite absorption layer. Therefore, the above-mentioned improvement strategy effectively improves the photoelectric conversion efficiency, light stability, and high humidity and high heat stability of perovskite solar cells, paving the way for the industrialization of perovskite solar cells.
[0011] Preferably, the oxidizing agent comprises an oxidizing acid and / or an oxidizing organic salt.
[0012] Preferably, the oxidizing acid comprises an oxidizing inorganic acid and / or an oxidizing organic acid.
[0013] Preferably, the oxidizing inorganic acid comprises perchloric acid and / or periodic acid.
[0014] Preferably, the hole transport layer is a nickel oxide layer.
[0015] Preferably, after the surface of the hole transport layer close to the passivation layer is modified by an oxidant, part of the Ni 2+ Oxidation to Ni 3+ , so that Ni in the hole transport layer 3+ The content of Ni 2+ and Ni 3+ The ratio of the total content is 0.75-0.85, for example, it can be 0.75, 0.76, 0.77, 0.78, 0.79, 0.8, 0.81, 0.82, 0.83, 0.84 or 0.85, etc.
[0016] In the present invention, the Ni content in the nickel oxide layer is increased to a certain extent. 3+ The content helps to significantly improve the conductivity of the nickel oxide layer.
[0017] Preferably, the thickness of the hole transport layer is 15-25 nm, for example, 15 nm, 20 nm, 25 nm, etc.
[0018] Preferably, the hafnium oxide has a crystal form of cubic phase.
[0019] In the present invention, in the cubic phase of hafnium oxide, the arrangement of atoms or ions is highly consistent in all directions, which makes the hafnium oxide show isotropy in physical and chemical properties. In optical applications, the cubic phase of hafnium oxide has more uniform optical properties.
[0020] Preferably, the thickness of the passivation layer is 0-2 nm, and is not 0, for example, it may be 0.1 nm, 0.3 nm, 0.5 nm, 0.7 nm, 1 nm, 1.2 nm, 1.5 nm, 1.6 nm, 1.8 nm or 2 nm, etc., preferably 0.8-1.6 nm.
[0021] In the present invention, a passivation layer with a suitable thickness is beneficial to preventing the nickel oxide surface modified by the oxidant from reacting with the perovskite solution while ensuring the carrier transport performance.
[0022] Preferably, the chemical formula of the perovskite absorption layer is ABX3, wherein A is any one of formamidinium ion, methylamine ion or cesium ion or a combination of at least two thereof, B is lead ion and / or tin ion, and X is a halogen ion. Exemplary examples include FAPbI3, MAPbI3, FA x Cs 1-x PbI3、FA x Cs 1-x PbI y Br 3-y 、FACsMAPbI y Br 3-y Or CsPbI3, etc., wherein the value range of x is 0.05-0.2, for example, it can be 0.05, 0.1, 0.13, 0.15, 0.18 or 0.2, etc., and the value range of y is 0-3, which can be 0, 1, 2 or 3, etc.
[0023] Preferably, the thickness of the perovskite absorption layer is 300-500 nm, for example, it may be 300 nm, 320 nm, 350 nm, 380 nm, 400 nm, 420 nm, 450 nm, 480 nm or 500 nm.
[0024] Preferably, the material of the electron transport layer includes titanium dioxide (TiO2), tin dioxide (SnO2), zinc-doped tin oxide (ZTO), cadmium sulfide (CdS), fullerene (C 60 ), magnesium-doped zinc oxide (ZMO), zinc oxide (ZnO) or PCBM ([6,6]phenyl-C 61 -methyl butyrate) or a combination of at least two thereof.
[0025] Preferably, the thickness of the electron transport layer is 5-50 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm.
[0026] Preferably, the conductive substrate is a transparent conductive glass, for example, ITO conductive glass or FTO (fluorine-doped tin oxide) conductive glass.
[0027] It should be noted that the present invention does not limit the material selection of the glass substrate in the transparent conductive glass. For example, it can be ultra-clear float glass, etc. Ultra-clear float glass refers to ultra-clear glass that has all the processability of high-quality float glass, and has excellent physical, mechanical and optical properties. It can be subjected to various deep processing like other high-quality float glass, such as tempering, coating, glaze, hot bending, lamination, hollow assembly, etc.
[0028] Preferably, the electrode is a metal electrode or a composite electrode. Exemplarily, the metal electrode may be any one of a Cu electrode, an Ag electrode or an Au electrode, or a combination of at least two thereof.
[0029] Preferably, the composite electrode comprises a transparent conductive layer and a metal layer stacked in a direction away from the conductive substrate.
[0030] Preferably, the material of the transparent conductive layer includes any one of tin-doped indium oxide (ITO), aluminum-doped zinc oxide (AZO), tungsten-doped indium oxide (IWO) or zinc-doped indium oxide (IZO), or a combination of at least two thereof.
[0031] Preferably, the material of the metal layer includes any one of Cu, Mo, Cr, Ag or Au, or a combination of at least two of them.
[0032] Preferably, the thickness of the transparent conductive layer is 15-200 nm, for example, 15 nm, 30 nm, 50 nm, 65 nm, 80 nm, 100 nm, 150 nm or 200 nm.
[0033] Preferably, the thickness of the metal layer is 15-100 nm, for example, 15 nm, 30 nm, 50 nm, 65 nm, 80 nm or 100 nm.
[0034] In a third aspect, the present invention provides a method for preparing an inverted perovskite solar cell as described in the first aspect, the preparation method comprising the following steps:
[0035] A hole transport layer is prepared on a conductive substrate, and then the surface of the hole transport layer is treated with an oxidant solution.
[0036] A passivation layer is prepared on the surface of the hole transport layer, and then a perovskite absorption layer and an electrode are sequentially prepared on the passivation layer to obtain the inverted perovskite solar cell.
[0037] Wherein, the material of the passivation layer is hafnium oxide.
[0038] Preferably, the concentration of the oxidant solution is 0.2-2wt%, for example, it can be 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2wt%, etc., preferably 0.1-1wt%.
[0039] In the present invention, an oxidant solution with a suitable concentration is helpful to improve the conductivity of the hole transport layer.
[0040] Preferably, the oxidant solution treatment method comprises the following steps:
[0041] The conductive substrate for preparing the hole transport layer is immersed in the oxidant solution, and after the immersion is completed, it is blown dry.
[0042] Preferably, the soaking time is 20-60 s, for example, 20 s, 30 s, 40 s, 50 s or 60 s, etc., preferably 20-40 s.
[0043] In the present invention, the appropriate soaking time is conducive to the optimal reaction between the oxidant solution and the nickel oxide, and the appropriate Ni 3+ content.
[0044] Preferably, during the soaking process, the temperature of the oxidant solution is 20-40°C, for example, 20°C, 30°C or 40°C.
[0045] Preferably, the preparation method of the passivation layer comprises any one of physical vapor deposition, chemical vapor deposition, reactive plasma deposition or solution deposition, or a combination of at least two thereof.
[0046] Preferably, the physical vapor deposition method includes any one of magnetron sputtering, electron beam evaporation, atomic layer deposition or vacuum thermal evaporation, or a combination of at least two of them.
[0047] Preferably, the chemical vapor deposition method includes a metal organic chemical vapor epitaxy (MOCVD) method or a plasma enhanced chemical vapor deposition (PECVD) method.
[0048] Preferably, the magnetron sputtering method includes any one of a radio frequency sputtering method, a direct current pulse method, a medium frequency sputtering method or a direct current sputtering method.
[0049] Preferably, the specific parameters of the radio frequency sputtering method include:
[0050] The target material is hafnium oxide material, the sputtering temperature is 20-60°C, for example, it can be 20°C, 30°C, 40°C, 50°C or 60°C, etc., the RF power is 1000-4000W, for example, it can be 1000W, 2000W, 3000W or 4000W, etc., the sputtering gas pressure is 0.04-0.6Pa, for example, it can be 0.04Pa, 0.1Pa, 0.2Pa, 0.3Pa, 0.4Pa, 0.5Pa or 0.6Pa, etc., and the sputtering frequency is 13-14MHz, for example, it can be 13MHz, 13.2MHz, 13.4MHz, 13.6MHz, 13.8MHz or 14MHz, etc.
[0051] Preferably, the sputtering gas of the radio frequency sputtering method includes an inert gas and oxygen. Exemplarily, the inert gas may be argon or the like.
[0052] Preferably, the preparation method of the perovskite absorption layer includes any one of a solution method, a spraying method, a blade coating method or a vacuum solution method.
[0053] Preferably, the preparation method comprises the following steps:
[0054] (1) A nickel oxide layer with a thickness of 15-25 nm is deposited on the surface of the conductive substrate, and then placed in an oxidizing inorganic acid solution with a concentration of 0.2-2wt% and allowed to stand for 20-60 seconds. The temperature of the oxidizing inorganic acid solution is 20-40°C during the standing period. After standing, the nickel oxide layer is blown dry to complete the surface treatment.
[0055] (2) A hafnium oxide layer having a thickness of 0-2 nm and not 0 is deposited on the surface treated nickel oxide layer by radio frequency sputtering, wherein the specific parameters include:
[0056] The target material is hafnium oxide, the sputtering temperature is 20-60°C, the RF power is 1000-4000W, the sputtering gas pressure is 0.04-0.6Pa, and the sputtering frequency is 13-14MHz.
[0057] (3) A perovskite wet film is scraped on the hafnium oxide layer by a scraping method, and then annealing is performed to form a perovskite absorption layer; wherein, in the scraping method, the scraping rate is 10-15 mm / s (for example, it can be 10 mm / s, 11 mm / s, 12 mm / s, 13 mm / s, 14 mm / s or 15 mm / s, etc.).
[0058] (4) An electron transport layer, a transparent conductive layer and a metal layer are sequentially prepared on the perovskite absorption layer to obtain an inverse perovskite solar cell.
[0059] Exemplarily, the method for preparing the nickel oxide layer may be any one of physical vapor deposition, chemical vapor deposition, reactive plasma deposition or solution method or a combination of at least two thereof, and the method for preparing the electron transport layer may be any one of physical vapor deposition, chemical vapor deposition, reactive plasma deposition or solution method or a combination of at least two thereof. The method for preparing the transparent conductive layer may be reactive plasma deposition or magnetron sputtering, and the method for preparing the metal layer may be magnetron sputtering or vacuum evaporation.
[0060] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0061] Compared with the prior art, the present invention has the following beneficial effects:
[0062] On the one hand, the present invention uses an oxidant to modify the surface of the hole transport layer, greatly improving the conductivity and hole transport capacity of the hole transport layer. On the other hand, hafnium oxide is introduced between the hole transport layer / perovskite absorption layer to passivate the interface. Since hafnium oxide has poor reactivity and carries a negative fixed charge, the chemical reaction between the modified hole transport layer and the perovskite absorption layer can be greatly reduced, inhibiting its degradation of the perovskite absorption layer, and effectively changing the concentration distribution of carriers near the heterojunction, thereby reducing the defect density at the interface, reducing interface recombination and photovoltage loss; and the passivation treatment of the passivation layer is conducive to the growth of perovskite and the uniform deposition of a large area perovskite absorption layer. Therefore, the above-mentioned improvement strategy effectively improves the photoelectric conversion efficiency, light stability, and high humidity and high heat stability of perovskite solar cells, paving the way for the industrialization of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is a schematic diagram of the structure of a perovskite solar cell provided in Example 1 of the present invention.
[0064] Among them, 1-FTO conductive glass; 2-nickel oxide layer; 3-passivation layer; 4-perovskite absorption layer; 5-C 60 layer; 6-SnO2 layer; 7-ITO layer; 8-Cu layer. DETAILED DESCRIPTION
[0065] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0066] Example 1
[0067] This embodiment provides an inverted perovskite solar cell, and its structural schematic diagram is as follows Figure 1 As shown, the inverted perovskite solar cell comprises a stacked FTO conductive glass 1, a nickel oxide layer 2, a passivation layer 3, a perovskite absorption layer 4, and a C 60 Layer 5, SnO2 layer 6, ITO layer 7 and Cu layer 8.
[0068] The surface of the nickel oxide layer 2 near the passivation layer 3 is modified by an oxidant, and the Ni 3+ The content of Ni 2+ and Ni 3+ The total content ratio is 0.8, the thickness of the nickel oxide layer 2 is 15 nm; the material of the passivation layer 3 is cubic hafnium oxide with a thickness of 0.8 nm; and the oxidant is perchloric acid.
[0069] The chemical formula of the perovskite absorber layer 4 is Cs 0.1 FA 0.9 PbI3, thickness 500nm; C 60 The thickness of the layer 5 is 20 nm, the thickness of the SnO2 layer 6 is 10 nm; the thickness of the ITO layer 7 is 30 nm, and the thickness of the Cu layer 8 is 80 nm.
[0070] This embodiment also provides a method for preparing the above-mentioned inverse perovskite solar cell, and the preparation method comprises the following steps:
[0071] (1) ultrasonically cleaning the FTO conductive glass with a glass cleaning agent and deionized water respectively, and fully drying it in an oven at 100° C., and repeating this process three times to obtain the FTO conductive glass;
[0072] Before the nickel oxide layer is deposited, the FTO conductive glass is treated with UV-ozone for 30 minutes and then enters the magnetron sputtering equipment;
[0073] (2) The background vacuum is less than 1×10 -3 When Pa, the amount of high-purity argon and argon oxygen mixed gas is set, and a radio frequency power supply is used to perform magnetron sputtering on the FTO conductive glass to deposit a nickel oxide layer with a thickness of 15 nm, and then placed in a 0.33wt% perchloric acid solution (the mass ratio of water to perchloric acid in the perchloric acid solution is 300:1) and allowed to stand for 20s. The temperature of the oxidizing inorganic acid solution is 25°C when it is still. After standing, it is blown dry to complete the surface treatment.
[0074] (3) A hafnium oxide layer with a thickness of 0.8 nm is deposited on the surface treated nickel oxide layer by radio frequency sputtering, and the specific parameters include:
[0075] The target material is hafnium oxide, the sputtering temperature is 40°C, the RF power is 1300W, the sputtering gas pressure is 0.1Pa, and the sputtering frequency is 13.56MHz.
[0076] (4) Using a scraping method, a 1.1 mol / L perovskite precursor solution is scraped onto the hafnium oxide layer to form a layer of chemical formula Cs 0.1 FA 0.9 The PbI3 perovskite wet film is blown away with nitrogen to remove excess solvent, and then annealed at 70°C for 2 minutes and at 120°C for 40 minutes to form a perovskite absorption layer; wherein, in the scraping method, the scraping rate is 12 mm / s.
[0077] (5) Using thermal evaporation method, the vacuum degree is less than 1×10 -4 Pa, a 20nm thick C layer is deposited on the surface of the perovskite absorber layer. 60 layer, and then the atomic layer deposition method is used with a vacuum degree of less than 1×10 -1 Pa, under C 60 A SnO2 layer with a thickness of 10 nm is deposited on the layer.
[0078] (6) Using DC sputtering, the vacuum degree is less than 1×10 -3 Under the condition of Pa, an ITO layer with a thickness of 30 nm and a Cu layer with a thickness of 80 nm are sequentially deposited on the surface of the SnO2 layer to obtain an inverse perovskite solar cell.
[0079] Example 2
[0080] This embodiment provides an inverted perovskite solar cell, which includes a stacked FTO conductive glass, a nickel oxide layer, a passivation layer, a perovskite absorption layer, a C 60 layer, SnO2 layer, ITO layer and Cu layer.
[0081] The surface of the nickel oxide layer close to the passivation layer is modified by an oxidant. 3+ The content of Ni 2+ and Ni 3+ The total content ratio is 0.75, the thickness of the nickel oxide layer is 20nm; the material of the passivation layer is cubic hafnium oxide with a thickness of 1.2nm; and the oxidant is periodic acid.
[0082] The chemical formula of the perovskite absorber is Cs 0.1 FA 0.9 PbI3, thickness 300nm; C 60 The thickness of the Si layer is 20 nm, the thickness of the SnO2 layer is 10 nm; the thickness of the ITO layer is 30 nm, and the thickness of the Cu layer is 80 nm.
[0083] This embodiment also provides a method for preparing the above-mentioned inverse perovskite solar cell, and the preparation method comprises the following steps:
[0084] (1) ultrasonically cleaning the FTO conductive glass with a glass cleaning agent and deionized water respectively, and fully drying it in an oven at 100° C., and repeating this process three times to obtain the FTO conductive glass;
[0085] Before the nickel oxide layer is deposited, the FTO conductive glass is treated with UV-ozone for 30 minutes and then enters the magnetron sputtering equipment;
[0086] (2) The background vacuum is less than 1×10 -3 Pa, set the amount of high-purity argon and argon oxygen mixed gas, and use a radio frequency power supply to perform magnetron sputtering on the FTO conductive glass to deposit a 20 nm thick nickel oxide layer, which is then placed in a 1 wt % perchloric acid solution (the mass ratio of water to perchloric acid in the perchloric acid solution is 99:1) and allowed to stand for 40 s. The temperature of the oxidizing inorganic acid solution is 25 ° C when it is still. After standing, blow dry to complete the surface treatment.
[0087] (3) A hafnium oxide layer with a thickness of 1.2 nm is deposited on the surface treated nickel oxide layer by radio frequency sputtering, and the specific parameters include:
[0088] The target material is hafnium oxide, the sputtering temperature is 40°C, the RF power is 1300W, the sputtering gas pressure is 0.1Pa, and the sputtering frequency is 13.56MHz.
[0089] (4) Using a scraping method, a 1.1 mol / L perovskite precursor solution is scraped onto the hafnium oxide layer to form a layer of chemical formula Cs 0.1 FA 0.9 The PbI3 perovskite wet film is blown away with nitrogen to remove excess solvent, and then annealed at 70°C for 2 minutes and at 120°C for 40 minutes to form a perovskite absorption layer; wherein, in the scraping method, the scraping rate is 12 mm / s.
[0090] (5) Using thermal evaporation method, the vacuum degree is less than 1×10 -4 Pa, a 20nm thick C layer is deposited on the surface of the perovskite absorber layer. 60 layer, and then the atomic layer deposition method is used with a vacuum degree of less than 1×10 -1 Pa, under C 60 A SnO2 layer with a thickness of 10 nm is deposited on the layer.
[0091] (6) Using DC sputtering, the vacuum degree is less than 1×10 -3Under the condition of Pa, an ITO layer with a thickness of 30 nm and a Cu layer with a thickness of 80 nm are sequentially deposited on the surface of the SnO2 layer to obtain an inverse perovskite solar cell.
[0092] Example 3
[0093] This embodiment provides an inverted perovskite solar cell, which includes a stacked FTO conductive glass, a nickel oxide layer, a passivation layer, a perovskite absorption layer, a C 60 layer, SnO2 layer, ITO layer and Cu layer.
[0094] The surface of the nickel oxide layer close to the passivation layer is modified by an oxidant. 3+ The content of Ni 2+ and Ni 3+ The total content ratio is 0.85, the thickness of the nickel oxide layer is 25nm; the material of the passivation layer is cubic hafnium oxide with a thickness of 1.6nm; and the oxidant is periodic acid.
[0095] The chemical formula of the perovskite absorber is Cs 0.1 FA 0.9 PbI3, thickness 400nm; C 60 The thickness of the Si layer is 20 nm, the thickness of the SnO2 layer is 10 nm; the thickness of the ITO layer is 30 nm, and the thickness of the Cu layer is 80 nm.
[0096] This embodiment also provides a method for preparing the above-mentioned inverse perovskite solar cell, and the preparation method comprises the following steps:
[0097] (1) ultrasonically cleaning the FTO conductive glass with a glass cleaning agent and deionized water respectively, and fully drying it in an oven at 100° C., and repeating this process three times to obtain the FTO conductive glass;
[0098] Before the nickel oxide layer is deposited, the FTO conductive glass is treated with UV-ozone for 30 minutes and then enters the magnetron sputtering equipment;
[0099] (2) The background vacuum is less than 1×10 -3 When Pa, the amount of high-purity argon and argon oxygen mixed gas is set, and a radio frequency power supply is used to perform magnetron sputtering on the FTO conductive glass to deposit a nickel oxide layer with a thickness of 25 nm, and then placed in a 2wt% perchloric acid solution (the mass ratio of water to perchloric acid in the perchloric acid solution is 49:1) and allowed to stand for 60s. The temperature of the oxidizing inorganic acid solution is 25°C when it is still. After standing, it is blown dry to complete the surface treatment.
[0100] (3) A hafnium oxide layer with a thickness of 1.6 nm is deposited on the surface treated nickel oxide layer by radio frequency sputtering, and the specific parameters include:
[0101] The target material is hafnium oxide, the sputtering temperature is 40°C, the RF power is 1300W, the sputtering gas pressure is 0.1Pa, and the sputtering frequency is 13.56MHz.
[0102] (4) Using a scraping method, a 1.1 mol / L perovskite precursor solution is scraped onto the hafnium oxide layer to form a layer of chemical formula Cs 0.1 FA 0.9 The PbI3 perovskite wet film is blown away with nitrogen to remove excess solvent, and then annealed at 70°C for 2 minutes and at 120°C for 40 minutes to form a perovskite absorption layer; wherein, in the scraping method, the scraping rate is 12 mm / s.
[0103] (5) Using thermal evaporation method, the vacuum degree is less than 1×10 -4 Pa, a 20nm thick C layer is deposited on the surface of the perovskite absorber layer. 60 layer, and then the atomic layer deposition method is used with a vacuum degree of less than 1×10 -1 Pa, under C 60 A SnO2 layer with a thickness of 10 nm is deposited on the layer.
[0104] (6) Using DC sputtering, the vacuum degree is less than 1×10 -3 Under the condition of Pa, an ITO layer with a thickness of 30 nm and a Cu layer with a thickness of 80 nm are sequentially deposited on the surface of the SnO2 layer to obtain an inverse perovskite solar cell.
[0105] Example 4
[0106] The difference between this embodiment and embodiment 1 is that the concentration of the perchloric acid solution in step (2) is 0.99 wt %, that is, the mass ratio of water to perchloric acid is 100:1.
[0107] The rest of the preparation methods and parameters were the same as those in Example 1.
[0108] Example 5
[0109] The difference between this embodiment and embodiment 1 is that the concentration of the perchloric acid solution in step (2) is 1.96 wt %, that is, the mass ratio of water to perchloric acid is 50:1.
[0110] The rest of the preparation methods and parameters were the same as those in Example 1.
[0111] Example 6
[0112] The difference between this embodiment and embodiment 1 is that the standing time in step (2) is 40 seconds.
[0113] The rest of the preparation methods and parameters were the same as those in Example 1.
[0114] Example 7
[0115] The difference between this embodiment and embodiment 1 is that the standing time in step (2) is 60 seconds.
[0116] The rest of the preparation methods and parameters were the same as those in Example 1.
[0117] Example 8
[0118] The difference between this embodiment and embodiment 1 is that the mass of the perchloric acid solution in step (2) is replaced by a periodic acid solution.
[0119] The rest of the preparation methods and parameters were the same as those in Example 1.
[0120] Example 9
[0121] The difference between this embodiment and embodiment 1 is that the standing time in step (2) is 10 seconds.
[0122] The rest of the preparation methods and parameters were the same as those in Example 1.
[0123] Example 10
[0124] The difference between this embodiment and embodiment 1 is that the standing time in step (2) is 70 seconds.
[0125] The rest of the preparation methods and parameters were the same as those in Example 1.
[0126] Embodiment 11
[0127] The difference between this embodiment and embodiment 1 is that the concentration of the perchloric acid solution in step (2) is 0.1 wt %, that is, the mass ratio of water to perchloric acid is 999:1.
[0128] The rest of the preparation methods and parameters were the same as those in Example 1.
[0129] Example 12
[0130] The difference between this embodiment and embodiment 1 is that the concentration of the perchloric acid solution in step (2) is 2.5 wt %, that is, the mass ratio of water to perchloric acid is 39:1.
[0131] The rest of the preparation methods and parameters were the same as those in Example 1.
[0132] Example 13
[0133] The difference between this embodiment and embodiment 1 is that the crystal form of hafnium oxide is tetragonal phase.
[0134] The rest of the preparation methods and parameters were the same as those in Example 1.
[0135] Embodiment 14
[0136] The difference between this embodiment and embodiment 1 is that the thickness of the passivation layer is 3 nm.
[0137] The rest of the preparation methods and parameters were the same as those in Example 1.
[0138] Comparative Example 1
[0139] The difference between this comparative example and Example 1 is that the nickel oxide layer is not subjected to surface treatment and the passivation layer is not deposited.
[0140] The rest of the preparation methods and parameters were the same as those in Example 1.
[0141] Comparative Example 2
[0142] The difference between this comparative example and Example 1 is that after the nickel oxide layer is prepared in step (2), it is not placed in a perchloric acid solution for surface treatment, but a hafnium oxide layer is directly deposited on the surface of the nickel oxide layer.
[0143] The rest of the preparation methods and parameters were the same as those in Example 1.
[0144] Comparative Example 3
[0145] The difference between this comparative example and Example 1 is that no passivation layer is provided, that is, step (3) is not performed.
[0146] The rest of the preparation methods and parameters were the same as those in Example 1.
[0147] Comparative Example 4
[0148] The difference between this comparative example and Example 1 is that in step (3), the hafnium oxide layer is replaced by a silicon oxide layer.
[0149] The rest of the preparation methods and parameters were the same as those in Example 1.
[0150] Performance Testing
[0151] The inverse perovskite solar cells provided in the above embodiments and comparative examples were subjected to photoelectric performance tests and stability tests.
[0152] The conditions for the photoelectric performance test include: testing under AM1.5 simulated sunlight, with an irradiance of 100mW·cm -2 , photoelectric conversion efficiency = (open circuit voltage × short circuit current × fill factor) / (cell area × illumination amplitude) × 100%.
[0153] The conditions of the stability test include: setting the maximum output power under simulated sunlight, 85° C., 85% RH (relative humidity), an aging time of 1000 h, and recording the difference between the photoelectric conversion efficiency after 1000 h and the photoelectric conversion efficiency in the initial state.
[0154] The test results are shown in Table 1.
[0155] Table 1
[0156]
[0157] analyze:
[0158] As can be seen from the above table, the present invention uses an oxidant to modify the surface of the hole transport layer, greatly improving the conductivity and hole transport capacity of the hole transport layer. On the other hand, hafnium oxide is introduced between the hole transport layer / perovskite absorption layer to passivate the interface. Since hafnium oxide has poor reactivity and carries a negative fixed charge, the chemical reaction between the modified hole transport layer and the perovskite absorption layer can be greatly reduced, inhibiting its degradation of the perovskite absorption layer, and effectively changing the concentration distribution of carriers near the heterojunction, thereby reducing the defect density at the interface, reducing interface recombination and photovoltage loss; and the passivation treatment of the passivation layer is conducive to the growth of perovskite and the uniform deposition of a large area of perovskite absorption layer. Therefore, the above-mentioned improvement strategy effectively improves the photoelectric conversion efficiency, light stability, and high humidity and high heat stability of perovskite solar cells, paving the way for the industrialization of perovskite solar cells.
[0159] It can be seen from Examples 1, 4-5 and 11-12 that a perchloric acid solution of appropriate concentration is conducive to producing a stable surface reaction. If the perchloric acid solution is too low, the reaction range will be localized rather than comprehensive and only a small amount of Ni will be generated. 3+ , which reduces the PCE and photothermal stability of the battery; if the perchloric acid solution is too high, it will cause abnormalities in the uniformity, crystallinity, solubility, etc. of the hole transport layer, affecting the interface properties and electrical properties, and reducing the PCE and photothermal stability of the battery.
[0160] It can be seen from Examples 1, 6-7 and 9-10 that a suitable standing time is beneficial to promoting the surface reaction with the hole transport layer and generating more Ni 3+ If the standing time is too short, the surface reaction will not be complete and sufficient Ni will not be generated. 3+ , which reduces the PCE and photothermal stability of the battery; if the standing time is too long, reaction by-products or impurities will be produced, which will reduce the PCE and photothermal stability of the battery.
[0161] It can be seen from Example 1 and Example 13 that if the crystal form of hafnium oxide is tetragonal, compared with the cubic phase, it will produce certain conductive properties, resulting in a mismatch in the energy level band gap between the passivation layer and the perovskite absorption layer, thereby causing a significant attenuation in stability performance.
[0162] It can be seen from Example 1 and Example 14 that if the thickness of the passivation layer is too thick, it is not conducive to carrier transmission, which is manifested as the short-circuit current of the initial conversion efficiency is too low, but it has a better attenuation performance in terms of photothermal aging stability.
[0163] It can be seen from Example 1 and Comparative Example 1 that if the nickel oxide layer is not surface treated and there is no passivation layer, the short-circuit current density of the battery is poor, resulting in poor photoelectric conversion efficiency of the battery, and the photothermal stability of the battery is significantly attenuated.
[0164] It can be seen from Example 1 and Comparative Example 2 that if the hafnium oxide layer is directly deposited on the surface of the nickel oxide layer without surface treatment, the short-circuit current will be too low, thereby affecting the photoelectric conversion efficiency of the initial device.
[0165] It can be seen from Example 1 and Comparative Example 3 that if the passivation layer is not provided, the initial device efficiency is better, but the photothermal aging attenuation data will be poor.
[0166] It can be seen from Example 1 and Comparative Example 4 that if the hafnium oxide layer is replaced by a silicon oxide layer, the structural defects and impurities in the production process can provide free electrons, thereby improving the conductivity of the material, which is not conducive to matching the energy level band gap between the hole transport layer and the perovskite interface.
[0167] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. An inverted perovskite solar cell, characterized in that: The inverted perovskite solar cell comprises a conductive substrate, a hole transport layer, a passivation layer, a perovskite absorption layer, an electron transport layer and an electrode arranged in a stacked manner; Wherein, the surface of the hole transport layer on one side close to the passivation layer is modified by an oxidant, and the material of the passivation layer is hafnium oxide.
2. The inverted perovskite solar cell according to claim 1, characterized in that: The oxidant includes an oxidizing acid and / or an oxidizing organic salt; Preferably, the oxidizing acid comprises an oxidizing inorganic acid and / or an oxidizing organic acid; Preferably, the oxidizing inorganic acid comprises perchloric acid and / or periodic acid; Preferably, the hole transport layer is a nickel oxide layer; Preferably, after the surface of the hole transport layer close to the passivation layer is modified by an oxidant, part of the Ni 2+ Oxidation to Ni 3+ , so that Ni in the hole transport layer 3+ The content of Ni 2+ and Ni 3+ The ratio of the total content is 0.75-0.85; Preferably, the hole transport layer has a thickness of 15-25 nm.
3. The inverted perovskite solar cell according to claim 1 or 2, characterized in that: The hafnium oxide has a crystal form of cubic phase; Preferably, the thickness of the passivation layer is 0-2 nm, and is not 0, and is preferably 0.8-1.6 nm.
4. The inverted perovskite solar cell according to any one of claims 1 to 3, characterized in that: The chemical formula of the perovskite absorption layer is ABX3, wherein A is any one of formamidinium ion, methylamine ion or cesium ion or a combination of at least two thereof, B is lead ion and / or tin ion, and X is a halogen ion; Preferably, the thickness of the perovskite absorption layer is 300-500 nm; Preferably, the material of the electron transport layer includes any one or a combination of at least two of titanium dioxide, tin dioxide, zinc-doped tin oxide, cadmium sulfide, fullerene, magnesium-doped zinc oxide, zinc oxide or PCBM; Preferably, the thickness of the electron transport layer is 5-50 nm; Preferably, the electrode is a metal electrode or a composite electrode; Preferably, the composite electrode comprises a transparent conductive layer and a metal layer stacked in a direction away from the conductive substrate; Preferably, the material of the transparent conductive layer includes any one of tin-doped indium oxide, aluminum-doped zinc oxide, tungsten-doped indium oxide or zinc-doped indium oxide, or a combination of at least two thereof; Preferably, the material of the metal layer includes any one of Cu, Mo, Cr, Ag or Au, or a combination of at least two thereof; Preferably, the thickness of the transparent conductive layer is 15-200 nm; Preferably, the thickness of the metal layer is 15-100 nm.
5. A method for preparing an inverse perovskite solar cell according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: A hole transport layer is prepared on a conductive substrate, and then a surface of the hole transport layer is treated with an oxidant solution; Preparing a passivation layer on the surface of the hole transport layer, and then sequentially preparing a perovskite absorption layer and an electrode on the passivation layer to obtain the inverted perovskite solar cell; Wherein, the material of the passivation layer is hafnium oxide.
6. The preparation method according to claim 5, characterized in that: The concentration of the oxidant solution is 0.2-2 wt %, preferably 0.1-1 wt %.
7. The preparation method according to claim 5 or 6, characterized in that: The method of treating the oxidant solution comprises the following steps: The conductive substrate for preparing the hole transport layer is immersed in the oxidant solution, and after the immersion is completed, it is blown dry.
8. The preparation method according to claim 7, characterized in that: The soaking time is 20-60s, preferably 20-40s; Preferably, during the soaking process, the temperature of the oxidant solution is 20-40°C.
9. The method according to any one of claims 5 to 8, characterized in that: The preparation method of the passivation layer includes any one of physical vapor deposition, chemical vapor deposition, reactive plasma deposition or solution method, or a combination of at least two thereof.
10. The preparation method according to any one of claims 5 to 9, characterized in that: The preparation method comprises the following steps: (1) depositing a nickel oxide layer with a thickness of 15-25 nm on the surface of the conductive substrate, and then placing it in an oxidizing inorganic acid solution with a concentration of 0.2-2 wt% and letting it stand for 20-60 seconds, the temperature of the oxidizing inorganic acid solution being 20-40° C. during the standing period, and then blowing it dry to complete the surface treatment; (2) A hafnium oxide layer having a thickness of 0-2 nm and not 0 is deposited on the surface treated nickel oxide layer by radio frequency sputtering, wherein the specific parameters include: The target material is hafnium oxide, the sputtering temperature is 20-60°C, the RF power is 1000-4000W, the sputtering gas pressure is 0.04-0.6Pa, and the sputtering frequency is 13-14MHz; (3) scraping a layer of perovskite wet film on the hafnium oxide layer by a scraping method, and then annealing to form a perovskite absorption layer; wherein the scraping method has a scraping rate of 10-15 mm / s; (4) An electron transport layer, a transparent conductive layer and a metal layer are sequentially prepared on the perovskite absorption layer to obtain an inverse perovskite solar cell.